Example of best practice: getting to the core of Red Apples-Green Apples: a dance and visual arts learning project between South Africa and Denmark. Issue 6 (2nd November 2021) - Wilson, Lisa; Vedel, Karen A.; Samuel, Gerard M.; Nielsen, Charlotte Svendler
ABSTRACT: This paper sets out to discuss pedagogical aspects of a collaborative project between Denmark and South Africa, two partner countries with a long history of educational partnerships. The project named Red Apples-Green Apples (RAGA) involved a joint group of facilitators from both countries exploring the topic of climate change and the nature elements (water, air, earth and fire), first with primary school children in Cape Town and then with children in Copenhagen, through the mediums of visual arts and dance. In both countries the children and facilitators were from diverse cultural backgrounds creating potentially rich opportunities for intercultural education alongside learning about the environment through the arts. The project in its pedagogical and structural design of shared artistic experiences enabled meaningful social interaction among the children and facilitators and resulted in enhanced knowledge, understanding and appreciation of self and others. This paper will argue that arts integration educational experiences, such as RAGA, grounded in core principles of 'collaboration', 'creativity', and 'cultural diversity' have the double capacity to enrich children's learning in and through the arts as well as nurture intercultural competences for both learners and teachers in the culturally diverse classroom.